Exploring the motivations, outcomes and influencing factors of researchers’ participation in science communication: A case study of "Science Festival " of Guangxi Academy of Sciences - Cai Shaofen (Education Research on Study Tours and Practice, 2025)
The participation of researchers is the key to improving the public’s scientific literacy and the quality of science communication. However, the current participation of researchers in science communication activities still has problems, such as low enthusiasm and uneven participation levels. In this paper we present a case study from the Science Festival organized by Guangxi Academy of Sciences (GXAS). It summarizes and examines in-depth interview data from 21 participating researchers, exploring their motivations for participation, outcomes, and influencing factors. The study reveals that researchers’ motivations for participation show a multi-layered structure, ranging from external to internal. These motivations include organizational arrangements, achievement display, learning and communication and so on. Researchers reported multiple types of outcomes, such as cognitive expansion across teams, emotional feedback, and knowledge improvement. At the same time, they faced challenges like time conflicts, lack of content innovation, and negative experiences. Key factors that promote participation include support from teams or leaders, personal development, social recognition, and positive engagement. The study suggests that future science communication should focus on stimulating researchers’ internal motivation while enhancing institutional support.